98
Пошаговое объяснение:
1. Упростим:
(2a-5)²+(5a-2)²= 4a²-20a+25+25a²-20a+4= 29a²-40a+29=
=29a²+29-40a= 29(a²+1)-40a.
2. Решаем
Если а=-1, то:
29(a²+1)-40a= 29•(1+1)+40=(29•2)+40= 98.
ответ: 98.
(Пояснение: в скобках 1+1 получилось, потому что(-1)²=-1×-1=1; 1+1=2
Пояснение: 40 получилось потому, что минус на минус дает знак плюс, -40•(-1)= 40).
98
Пошаговое объяснение:
1. Упростим:
(2a-5)²+(5a-2)²= 4a²-20a+25+25a²-20a+4= 29a²-40a+29=
=29a²+29-40a= 29(a²+1)-40a.
2. Решаем
Если а=-1, то:
29(a²+1)-40a= 29•(1+1)+40=(29•2)+40= 98.
ответ: 98.
(Пояснение: в скобках 1+1 получилось, потому что(-1)²=-1×-1=1; 1+1=2
Пояснение: 40 получилось потому, что минус на минус дает знак плюс, -40•(-1)= 40).